Effect of Socialization Group Activities Therapy Sociodrama on Loneliness Level For Elderly at Panti Werdha Sosial Tresna and Pemeliharaan Taman Makam Pahlawan Ciparay Kabupaten Bandung - Andria Pragholapati; Rizki Muliani; Haerul Imam; Iik Frida Haryana (Universitas Respati Yogyakarta, 2020)
The need to provide quality mental health care for elders in nursing home settings has been a critical issue, as the aging population grows rapidly and institutional care becomes a necessity for some elders. Loneliness is a problem that associate with age. Sociodrama, part of socialization group activities type, is one of treatment for loneliness elderly for helping client to socialize with others individuals and environment around them as well as helping re-form personality, international relationship, conflict, and emotional problem that would be explored by specific dramatic method. This study has aim to identify effect of sociodrama as one of socialization group activities therapy on loneliness level for eldery at Panti Werdha Sosial Tresna (BPSTW) and Pemeliharaan Taman Makam Pahlawan Ciparay Kabupaten Bandung. The research design used in this study, is quasi experimental by one group pretest-posttest design. In addition, 30 elderly who has problem with loneliness was selected to be sample by total sampling on this patients at the BPSTW and Pemeliharaan Taman Makam Pahlawan Bandung. For measuring loneliness, The UCLA Loneliness Scale used to see its level 2 times on pre and post treatment. Elderly is treated by sociodrama at 5 sessions during a week and each treatment needs time around 30 minutes. Data analyses used to paired sample t-test. The study showed most of elderly on the moderate loneliness on pre-treatment whereas half of them on the not lonely level after treatment. A significant correlation was found between pretest and posttest treatment with P value (0,000 ) < α (0,05) by paired sample t-test analyses concluded to emerge effect of treatment on the loneliness. Hopefully, this research could emerge any topics to further research in the future that could be applied on lonely elderly at BPSTW and Taman Makam Pahlawan Ciparay Kabupaten Bandung especially and around the world generally.